The pathogenicity and antibiotic resistance of coagulase-negative Staphylococci isolated from the maxillary and ethmoid sinuses - Aral, M; Keles, E; Okur, E; Alpay, HC; Yilmaz, M (Int Rhinologic Soc, 2004)
Aim of the study: To investigate the pathogenicity and antibiotic resistance of coagulase-negative staphylococci (CNS) isolated from the maxillary and ethmoid sinuses of patients undergoing endoscopic sinus surgery for chronic sinusitis. Patients and methods: Ninety-three patients (63 males, 30 females) aged between 19 - 68 years, who had undergone functional endoscopic sinus surgery (FESS) for chronic sinusitis, were included in the study. Nasal mucosa, skin anti adjacent structures were cleansed with povidone-iodine solution before surgery to prevent a probable contamination. In all patients, nasal swabs were taken before and after the application of povidone-iodine solution. Colonies isolated and identified as Staphylococci in cultures were further investigated for pathogenicity and antibiotic susceptibility. Slime test was used to determine the pathogenicity of CAS. The relationship between antibiotic resistance of pathogenic and non-pathogenic CNS was compared by X-2 analysis. Results: While bacterial growth rate was 62.3% in nasal swab cultures taken before the application of povidone-iodine solution, it decreased to 12.9% after the application of solution. Microorganisms were isolated in 95.6% of cultures taken from maxillary sinuses and in 91.3% of cultures obtained from ethmoid sinuses during the FESS. The most frequently isolated microorganism in each of the sinuses was CNS. Slime test was carried out in 30 CNS isolated. Twelve of these were slime positive and 18 were slime negative. While 83.3% of CNS isolated was resistant to penicilin, all of CNS were sensitive to vancomycin and teikoplanine. The difference between slime positive and slime negative CNS gentamicin and ciprofloxacin resistance was statistically significant (p<0.05). Conclusion: We consider that the pathogenicity tests, like slime production and antimicrobial susceptibilities of CNS frequently isolated from the patients with chronic sinusitis should be investigated and also these microorganisms should be kept in mind in the selection of empiric treatment.
Keywords: chronic sinusitis; CNS; pathogenicity; antibiotic resistance